A Randomized Trial of Mobile Health Support for Heart Failure Patients and Their Informal Caregivers. Issue 8 (August 2015) - Piette, John D.; Striplin, Dana; Marinec, Nicolle; Chen, Jenny; Aikens, James E.
<x xml:space="preserve">Abstract</x> Background: Mobile health services may improve chronic illness care, but interventions rarely support informal caregivers' efforts. Objectives: To determine whether automated feedback to caregivers of chronic heart failure patients impacts caregiving burden and assistance with self-management. Research Design: Randomized comparative effectiveness trial. Subjects: A total of 369 heart failure patients were recruited from a Veterans Health Administration health care system. All patients participated with a "CarePartner" or informal caregiver outside their household. Intervention: Patients randomized to "standard mHealth" received weekly automated self-care support calls for 12 months with notifications about problems sent to clinicians. "mobile health+CarePartner" (mHealth+CP) patients received identical services, plus email summaries and suggestions for self-care assistance automatically sent to their CarePartners. Measures: At baseline, 6, and 12 months, CarePartners completed assessments of caregiving strain, depressive symptoms, and participation in self-care support. Results: mHealth+CP CarePartners reported less caregiving strain than controls at both 6 and 12 months (both P⩽0.03). That effect as well as improvements in depressive symptoms were seen primarily among CarePartners reporting greater burden at baseline (P⩽0.03 for interactions between arm and baseline strain/depression at both endpoints). Although most mHealth+CP CarePartners increased the amount of time spent in self-care support, those with the highest time commitment at baseline reported decreases at both follow-ups (all P<0.05). mHealth+CP CarePartners reported more frequently attending patients' medical visits at 6 months (P=0.049) and greater involvement in medication adherence at both endpoints (both P⩽0.032). Conclusions: When CarePartners experienced significant caregiving strain and depression, systematic feedback about their patient-partner decreased those symptoms. Feedback also increased most CarePartners' engagement in self-care.